2019
DOI: 10.32709/akusosbil.505786
|View full text |Cite
|
Sign up to set email alerts
|

Paternalist Liderliğin Örgütsel Adalet Algısı Üzerine Etkisi: Sağlık Çalışanları Üzerinde Bir Araştırma

Abstract: Bu araştırma, sağlık yöneticilerin paternalist liderlik davranışlarının, çalışanların örgütsel adalet algısı üzerindeki etkisini incelemek amacı ile yapılmıştır. Bu araştırmada, sağlık çalışanlarının sosyodemografik özelliklerini tespit etmek için Kişisel Bilgi Formu, paternalist liderlik algısını ölçmek için Pellegrini ve Scandura ( 2006) tarafından geliştirilen Paternalist Liderlik Ölçeği ve örgütsel adalet algısını ölçmek için Niehoff ve Moorman (1993) tarafından geliştirilen Örgütsel Adalet Ölçeği kullanıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…While previous studies have shown paternalistic leadership to pave the way for adverse outcomes such as leader bullying (Soylu, 2011) or higher turnover (Liao, Widowati, Hu, & Tasman, 2017), they have also shown PL to be able to lead to positive employee behaviors such as creativeness (Kurt & Yahyagil, 2015) and organizational citizenship behaviors (Mete & Serin, 2015) as well as positive attitudes such as job satisfaction (Nal & Tarım, 2019) and organizational commitment (Erben & Güneşer, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While previous studies have shown paternalistic leadership to pave the way for adverse outcomes such as leader bullying (Soylu, 2011) or higher turnover (Liao, Widowati, Hu, & Tasman, 2017), they have also shown PL to be able to lead to positive employee behaviors such as creativeness (Kurt & Yahyagil, 2015) and organizational citizenship behaviors (Mete & Serin, 2015) as well as positive attitudes such as job satisfaction (Nal & Tarım, 2019) and organizational commitment (Erben & Güneşer, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the literature, there are findings supporting this opinion. In the study findings of Nal and Sevim [34], it has been determined that paternalist leadership has a significant and positive effect on the external motivation of the trainers. Paternalist management style encourages subordinates' business identity and reveals their motivation.…”
Section: Discussionmentioning
confidence: 97%
“…When the literature on the relationship between leadership and motivation is examined, it is possible to come across different results in many studies, with various types of leadership. Research findings show that leaders generally use motivational tools to meet followers' high-level needs, increase employees' internal and external motivation levels and intercultural self-motivation (Budak andBudak, 2010, Wang andGagné, 2013;Nal and Sevim, 2019;İskit, 2019;Kahya, 2020;Songur and İnce, 2020). However, it has been observed that the expertise and charismatic power of the leader has a stronger effect on employee motivation compared to other power sources (Tezcan, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the relationship between leadership and motivation, it is possible to come across studies investigating the relationship between various types of leadership and motivation. The main ones are general leadership studies (Khaliq, Usman and Ahmed, 2021;Galperin, Lituchy, Acquaah, Bewaji and Ford, 2014;Tezcan, 2006;Kurt, 2013, Bulut andÇavuş, 2015;Büyükdoğan and Arslanoğlu, 2017;Vural, 2016), while the others are researches on the transformational leadership (Kahya, 2020;Songur and İnce, 2020), authentic leadership (Aydınoğlu, 2020;Özerten, 2018), paternalistic leadership (Aydınoğlu, 2020;Nal and Sevim, 2019), charismatic leadership (Khaliq et al, 2021;Tezcan, 2006), toxic leadership (İskit, 2019), transactional leadership, and liberating leadership (Songur and İnce, 2020). However, it is seen that research on the relationship between leadership and motivation is mostly conducted by school administrators and schools (Kahya, 2020;Özerten, 2018;Vural, 2016;Büyükdoğan and Arslanoğlu, 2017;Ergen, 2009;Kurt, 2013;Ugar, 2019).…”
Section: Introductionmentioning
confidence: 99%